"Precarity" of the Territorialized State: Immigrants Re-drawing and Re-mapping the Borders. Issue 4 (1st October 2016) - Yildiz, Ugur
ABSTRACT: Any narrative on borders at the outset tends to begin with the Westphalian inclusionary and exclusionary system of nation-state through oftentimes highlighting the constructed nature of the mapping and drawing territorially defined landscapes. In its general notion, the concretization of borders simultaneously brings the system of nation-state which has fundamentally divided world into societies and states and has represented the regime of border as historically natural. The aim of this article is to approach this concrete and historically constructed phenomenon from the perspective of migrants with a focus on their acts of border crossing. The rationale of the article is two-fold— first, theoretical exploration and conceptualization of the border: the border as a space of heterotopia, the border as a liminal space or liminality, and the border as representational space . Second, the article aims to combine theoretical conceptualization with the empirical case. The article aims to explore the way of re-mapping, re-drawing, and re-shaping of borders by the agency of Other through concentrating on the perception of migrants and asylum seekers who are seeking asylum in Turkey and waiting to be resettled to a third safe country, here Canada. Through focusing on the migrants' mappings of these non-real and non-utopian places via semi-structured interviews conducted in Turkey, the paper aims to re-draw and re-shape the permeability and contingency of borders through visualizing phenomenological experience of individuals on the route and at the borders.